The Efficacy and Safety of Dingkun Pill in Women with Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (24th August 2022) - Jin, Bao; Zhang, Yang; Zhang, Zongyu; Yang, Guorong; Pan, Yujia; Xie, Liangzhen; Liu, Jiarui; Shen, Wenjuan
Abstract : Objective . Dingkun Pill (DKP) is a proprietary Chinese medicine that has been utilized for patients with gynecological diseases, and its clinical application has been widely accepted in China. However, the effects of DKP on reproduction and metabolism in women with polycystic ovary syndrome (PCOS) have never been systematically evaluated. Our objective was to evaluate the efficacy and safety of DKP in treating reproductive and metabolic abnormalities with PCOS. Methods . We searched in PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure, Wanfang Database, VIP Database, and Chinese Biomedical Literature Database up until January 2022 to identify randomized controlled trials (RCTs). The methodological quality of the included RCTs was estimated using the Cochrane collaboration risk-of-bias instrument, and the meta-analysis was performed using RevMan. Results . A total of 22 RCTs (including 1994 participants) were identified. DKP, combined with ovulation-inducing drugs (OID) or combined oral contraceptives (COC) was superior to OID or COC alone in improving the pregnancy rate (relative risk (RR) 1.84, 95% CI 1.62 to 2.11 and RR 1.38, 95% CI 1.16 to 1.64, respectively), ovulation rate (RR 1.38, 95% CI 1.03 to 1.84 and RR 1.23, 95% CI 1.11 to 1.37, respectively), endometrial thickness (weighted mean difference (WMD) 2.50, 95% CI 1.91 to 3.09 and WMD 0.62, 95% CI 0.08 to 1.16, respectively), luteinizing hormone (WMD −1.93, 95% CI −2.80 to−.07 and WMD −1.79, 95% CI −2.66 to−0.92, respectively), and testosterone (standardized mean difference (SMD) −2.12, 95% CI −3.01 to−1.24 and SMD −1.21, 95% CI −1.64 to−0.78, respectively). DKP combined with COC led to a greater improvement in homeostasis model assessment- β (WMD 20.42, 95% CI 16.85 to 23.98) when compared with COC alone. There was a significant difference between DKP and COC in terms of decreasing total cholesterol (WMD −0.37, 95% CI −0.72 to−0.02), triacylglycerol (WMD −0.85, 95% CI −1.50 to−0.20), and free fatty acid (WMD −130.00, 95% CI −217.56 to−42.22). However, DKP did not affect the follicle stimulating hormone, fasting blood glucose, fasting insulin, body mass index, waist-to-hip ratio, high-density lipoprotein cholesterol, or low-density lipoprotein cholesterol. Adverse reactions were more common in COC alone compared to DKP and COC in combination (RR 0.22, 95% CI 0.07 to 0.63). Conclusion . DKP shows promise in modifying reproductive and metabolic parameters in patients with PCOS and may be used as a primary choice in conventional or complementary therapies for PCOS. The quality of the evidence analyzed was suboptimal, and therefore, our results should be interpreted cautiously. More prospective large-scale and well-designed RCTs, as well as longer intervention durations are required in the future to draw more reliable conclusions.